Physicochemical Characteristics of Sun-dried and Roasted Cassava Rice - Rudiati Evi Masithoh; Maynanda Brigita Chrysta; Sabila Avinda Deviana (agriTECH, 2019)
High demand of rice can be minimized by promoting cassava as an alternative carbohydrate source. One method to process cassava to ease consumption and to prolong its shelf-life is by making it into analog rice, namely cassava rice. Two drying methods were studied to obtain the physicochemical information of cassava rice. This research aimed at determining color and chemical properties, i.e. water content, ash, lipid, protein, carbohydrate, starch, amylose, amylopectin, and mineral contents of cassava rice processed by roasting and sun-drying. It also compared physicochemical characteristics of cassava rice and paddy rice to get better understanding of nutritional values of cassava rice. Results showed that physical, chemical, and mineral contents of cassava rice were different from paddy rice. Cassava rice had lower water, protein, Zn and P2O5 contents than paddy rice. Roasted cassava rice was darker than cassava rice. Sun-dried and roasted cassava rice showed no different values in terms of lipid, carbohydrate, starch, amylose, amylopectin, Mg, Zn and P2O5 contents, while other characteristics were similar.